ANALISIS FILOSOFIS SENJATA TRADISIONAL LAMPUNG : KERIS - Apriana Apriana; Arya Putra Nugraha (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This culture includes customs that regulate daily life, regional languages ​​that are rich in local vocabulary, dance arts such as the Kancet Ledo Dance that depicts harmonious movements with nature, music such as the gendang beleq that accompanies ceremonies, the nuwo sesat traditional house that represents traditional architecture, and ceremonies such as Tulung Buyut that strengthen social ties. This study explores the Lampung keris as a complex and essential cultural symbol in Lampung society, Indonesia. Lampung culture, rich in traditions and noble values, faces the challenges of modernisation that threaten the loss of cultural identity. Using qualitative descriptive methods, the study identifies two main types of keris and describes their functions as status symbols and ritual tools. Cultural acculturation is reflected in the design of the keris, which adopts local elements and outside influences. The findings indicate the need for effective preservation strategies, such as local education and cultural promotion, to maintain the relevance of the keris not only as a tool but also as a link to the identity and heritage of the Lampung people amid changing times.